An IoT-Enabled Bicycle Access and Monitoring System with Geo-Fence-Based Location Restriction - Christian, Hans; Yusuf, Yohanes Gunawan; Ainul, Rafina Destiarti (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Managing shared bicycle usage within a university campus can be challenging, especially when relying on manual systems that are slow, difficult to track, and offer limited security. This paper propose the development of an IoT-based Bicycle Access and Monitoring System designed to make borrowing bikes easier for users and more manageable for campus administrators. The system allows users to borrow bicycles independently through a mobile application developed for Android devices. Each bicycle is equipped with a QR code, which users scan to initiate the borrowing process. After scanning, the application generates a One-Time Password (OTP), which is entered into a keypad embedded on the bicycle. After successful verification, the bicycle is automatically unlocked. To ensure bicycles remain within the designated campus boundaries, the system includes a geo-fencing feature that continuously monitors GPS coordinates. If a bicycle crosses the predefined boundary, the system triggers an alert and logs the event to a cloud-based database. All borrowing data including time, user ID, and location, are recorded in real time and accessible by campus administrators via a web interface. According experimental result show that the system functions reliably, with successful access control, accurate event logging, and an average GPS horizontal error of 1.48 meters. The proposed system provides a scalable, secure, and user-friendly solution for improving bicycle-sharing system in university area, enhancing both operational efficiency and student convenience.